COMPARATIVE LEGAL ANALYSIS OF SURROGACY BETWEEN INDONESIA AND INDIA - Muh Endriyo Susila; Kirthie Rubini Morgan (Faculty of Law Universitas Padjadjaran, 2022)
As a form of assisted reproduction methods, surrogacy remains controversial today. The practice of using surrogates has been around for very long time and serves a wide variety of functions in countries all over the world. The purpose of this research is to ascertain whether or not surrogacy is permissible under the laws that have been enacted and are in effect in Indonesia to govern the processes involved in surrogacy. This research also intends to determine whether or not surrogacy is allowed in India and analyze the legislative framework of that country in comparison to that of Indonesia. The type of research is normative legal research which relies on secondary data, in the form of legal material especially primary and secondary legal materials. This normative legal research employs both statutory and comparative approaches. Comparison is made between Indonesia and India. It is found that India has legalized the practice of surrogacy since long time ago. In addition, surrogacy in India does not only serve the reproductive purpose but also commercial purpose. On the other side, although the practices of surrogacy are also found in Indonesia, however, it remains illegal so far in this country.